Recent advances in noble metal free doped graphitic carbon nitride based nanohybrids for photocatalysis of organic contaminants in water: A review - Hasija, Vasudha; Raizada, Pankaj; Sudhaik, Anita; Sharma, Kirti; Kumar, Abhinandan; Singh, Pardeep; Jonnalagadda, Sreekantha B.; Thakur, Vijay Kumar (Elsevier, 2019)
Extensive contamination of water bodies by textile dyeing industries, organic pollutants and agricultural waste has emerged water pollution as one of the major global environmental crisis. The effect of this gross negligence is posing serious threats to human health therefore today; conserving water resources for the essence of life is of grave concern. Recently, advancements in photocatalytic properties of graphitic carbon nitride (g-C3N4) for wastewater treatment have gained tremendous interest in research. However, pristine g-C3N4 suffers from bottlenecks such as low surface area, rapid recombination of photo-generated electron–hole pairs and insufficient light absorption which thereby, reduces the photocatalytic degradation activity. Hitherto, noble metals have been widely utilized as dopants but are cost ineffective, rarely found and are difficult to recover. In this updated and all-inclusive review we have briefly discussed photocatalysis mechanism, primarily focused on non-precious elemental doping via various synthesis techniques of noble metal free doped g-C3N4 photocatalysts. Typically metal, non-metal, rare earth metal doping and co-doping have been explored, which demonstrates the synergistic behavior of the doped nanocomposites in modulation of electronic structure, broaden the visible light absorption range, enhancement in photocatalytic wastewater remediation ability to obtain maximum pollutant eradication. Summary remarks conclude the review with valuable knowledge of noble metal free doped g-C3N4 photocatalysts for water purification and sheds light on current challenges and crucial issues associated with its commercialization. The future aspect aims at designing of efficient solar light driven photocatalysts for application in various domains i.e. production of H2 and O2, reduction of CO2, practical use of solar cells, treatment of wastewater, air purification and environmental conservation
Keywords: Graphitic carbon nitride (g-C3N4); Inherent drawbacks of g-C3N4 as photocatalyst; Noble metal free doping of g-C3N4; Improved photocatalytic activity; Wastewater treatment